Genomic and Chemical Investigation of Bioactive Secondary Metabolites From a Marine-Derived Fungus Penicillium steckii P2648 - Yao, Guangshan; Chen, Xiaofeng; Zheng, Huawei; Liao, Danhua; Yu, Zhi; Wang, Zonghua; Chen, Jianming (Frontiers in Microbiology, 2021)
Marine fungi of the genus Penicillium are rich resources of secondary metabolites, showing a variety of biological activities. Our anti-bacterial screening revealed that the crude extract from a coral-derived fungus Penicillium steckii P2648 showed strong activity against some pathogenic bacteria. Genome sequencing and mining uncovered that there are 28 secondary metabolite gene clusters in P2648, potentially involved in the biosynthesis of antibacterial compounds. Chemical isolation and structural determination suggested citrinin is the dominant component of the crude extracts of P2648, and our further tests confirmed that citrinin showed excellent activities against various pathogenic bacteria. Moreover, the gene cluster containing a homolog of the polyketide synthase CitS was identified as the citrinin biosynthesis gene cluster through genetic analysis. Interestingly, three isoquinoline alkaloids were unexpectedly activated and isolated from the Δcits mutant and structural determination by using high-resolution electron spray ionization mass spectroscopy (HRESIMS), 1D, and 2D NMR. Further antibacterial assays displayed that compounds 1 and 2, but not compound 3, showed moderate activities against two antibiotic-resistant pathogenic bacteria with minimum inhibitory concentration (MIC) of 16–32 μg/ml. In conclusion, our results demonstrated that citrinin and isoquinoline alkaloids represent as the major antibacterial agents in the coral-associated fungus P. steckii P2648, and our genomic and chemical analyses present evidence in support of P. steckii P2648 as a potent natural products source for anti-bacterial drug discovery.